Mapping a historic neighbourhood through user-generated content: the case of Alfama, Lisbon (Portugal) - Tang, Vicente (2022)
Tang, V., Puri, J., & Painho, M. (2022). Mapping a historic neighbourhood through user-generated content: the case of Alfama, Lisbon (Portugal). In E. Parseliunas, A. Mansourian, P. Partsinevelos, & J. Suziedelyte-Visockiene (Eds.), Proceedings of the 25th AGILE Conference on Geographic Information Science, 2022 (Vol. 3, pp. 1-8). (AGILE: GIScience Series; Vol. 63). https://doi.org/10.5194/agile-giss-3-63-2022